Seagrass Meadows Reduce Wind-Wave Driven Sediment Resuspension in a Sheltered Environment - Contti Neto, Nery; Pomeroy, Andrew; Lowe, Ryan; Ghisalberti, Marco (Frontiers in Marine Science, 2022)
Seagrass meadows are prominent in many coastal zones worldwide and significant contributors to global primary production. The large bottom roughness (or canopy) created by seagrass meadows substantially alters near-bed hydrodynamics and sediment transport. In this study, we investigate how a seagrass meadow in a low-energy environment (forced by local winds) modifies near-bed mean and wave-driven flows and assess how this relates to suspended sediment concentration (SSC). A two-week field study was conducted at Garden Island in southwestern Australia, a shallow and sheltered coastal region subjected to large diurnal sea-breeze cycles, typical of many low-energy environments where seagrasses are found. The mean and turbulent flow structure, along with optical estimates of SSC, were measured within both a seagrass canopy and over an adjacent bare bed. Near-bed mean current velocities within the seagrass canopy were on average 35% of the velocity above the canopy. Oscillatory wave velocities were less attenuated than mean current velocities, with near-bed values on average being 83% of those above the canopy. Mean and maximum shear velocities inferred from currents and waves above the canopy frequently exceeded the threshold for sediment resuspension, but no significant variation was observed in the SSC. However, a significant correlation was observed between SSC and bed shear stress estimated using near-bed velocities inside the canopy. When sediment was resuspended, there were substantial differences between the SSCs within and above the canopy layer, with higher levels confined within the canopy. This study demonstrates the importance of measuring near-bed hydrodynamic processes directly within seagrass canopies for predicting the role seagrass meadows play in regulating local rates of sediment resuspension.